Influence of Phototherapy on the Kinetics of Orthodontic Tooth Movement: A Meta-Analysis of Randomized Controlled Trials - Salvador-Recolito, Maria Cynthia; Bierbaum, Susanne; Wolf-Brandstetter, Cornelia (Archive of Orofacial Data Science, 2024)
AIM: This study aims to evaluate the efficacy and safety of phototherapy and the correlation between its parameters in accelerating orthodontic tooth movement. METHODS: A comprehensive search was conducted across several databases from the study’s inception to January 25, 2019. Only randomized placebo-controlled trials examining adjunctive phototherapy during orthodontic canine retraction were included. Study quality was assessed using the Jadad score and the Cochrane risk of bias tool. Statistical analysis was performed using comprehensive meta-analysis software v. 3. RESULTS: A total of 21 studies involving 302 patients were eligible; 11 were included in the quantitative synthesis. A meta-analysis of low-quality evidence demonstrated that adjunctive phototherapy outperformed the control group (Hedges’ g = 0.68, 95% CI [0.08-1.28], I2 = 83%, p = 0.03). Subgroup analyses indicated more significant effects with a 940 nm wavelength (Hedges’ g = 2.93, 95% CI [2.20-3.65], I2 = 0%, p = 0.00), 100 mW output power (Hedges’ g = 1.17, 95% CI [-0.20-2.55], I2 = 91%, p = 0.10), and 5 J/cm2 energy density (Hedges’ g = 0.69, 95% CI [-0.03-1.41], I2 = 10%, p = 0.06). No risks were identified in the six studies that conducted safety investigations. CONCLUSION: Phototherapy can accelerate orthodontic tooth movement without associated risks. Significant effects were observed with higher dosages. Further well designed, high-quality trials are necessary to identify the exact impact of phototherapy and its parameters.